Extracellular vesicle‐packaged miR‐181c‐5p from epithelial ovarian cancer cells promotes M2 polarization of tumor‐associated macrophages via the KAT2B/HOXA10 axis. (19th September 2022) - Yang, Shuyan; Zhao, Honghui; Xiao, Wei; Shao, Lei; Zhao, Chunyan; Sun, Pengcheng
Abstract: Objectives: The molecular mechanistic actions of tumor‐derived extracellular vesicles (EVs) in modulating macrophage polarization in the tumor microenvironment of epithelial ovarian cancer (EOC) is largely unknown. The study was performed to clarify the effect and downstream mechanism of microRNA‐181c‐5p (miR‐181c‐5p)‐containing EVs from EOC cells in the M2 polarization of tumor‐associated macrophages (TAMs). Methods: EVs were isolated from normoxic and hypoxic human EOC cells SKOV3. Human mononuclear cell THP‐1 was induced by phorbol‐12‐myristate‐13‐acetate to differentiate into TAMs. The targeting relationship between miR‐181c‐5p and KAT2B was verified by dual luciferase reporter gene assay. The interaction between KAT2B and HOXA10 was detected by immunofluorescence, Co‐IP and ChIP assays. EdU staining, the scratch test and Transwell assay were used to assess the resultant cell proliferation, migration and invasion. The mouse xenograft model and the pulmonary metastasis model were developed through intraperitoneal injection of SKOV3 cells and tail vein injection of THP‐1 cells, respectively. Results: Hypoxic SKOV3 cell‐derived EVs could be internalized by TAMs. SKOV3 cell‐derived EVs induced by hypoxia (H‐EVs) promoted M2 polarization of TAMs and facilitated the proliferation, migration and invasion of SKOV3 cells. miR‐181c‐5p was highly expressed in H‐EVs and promoted the M2 polarization of TAMs. Further, miR‐181c‐5p targeted KAT2B, upregulated HOXA10 and activated the JAK1/STAT3 pathway, thereby promoting the M2 polarization of TAMs. In both mouse models, H‐EV‐derived miR‐181c‐5p promoted growth and metastasis of EOC cells. Conclusion: The miR‐181c‐5p‐containing EVs from hypoxic EOC cells may upregulate HOXA10 by targeting KAT2B and activate the JAK1/STAT3 pathway to promote the M2 polarization of TAMs, ultimately promoting growth and metastasis of EOC cells in vitro and in vivo . Abstract : Schematic illustration of molecular mechanism of miR‐181c‐5p loaded by EVs in hypoxic epithelial ovarian cancer. miR‐181c‐5p delivered by hypoxic epithelial ovarian cancer cell‐derived EVs targets KAT2B to upregulate HOXA10 and activate the JAK1/STAT3 pathway, thereby promoting the M2 polarization of TAMs and thus stimulating the growth and metastasis of epithelial ovarian cancer.